Resisting the Reflection: Identity in Inclusive Life History Research - Bj, Krist (Disability Studies Quarterly, 2010)
This article addresses the issue of identity production and reproduction in relation to social participation of young adults with intellectual disabilities. It is based on life history research conducted in collaboration with young adults with intellectual disabilities in Iceland. The article challenges the usefulness of the intellectual disability label and examines how the participants resist the label by telling stories of competence and abilities. The article also explores the interplay of the intellectual disability label and other social categories, such as class and religion. It concludes with a call for more awareness of the effects that non-disabled professionals and researchers have on the intellectual disability identity by using a label that is grounded in a deficit understanding of disability.